Effects of Lead Acetate on Morphology of Musca domestica L. (Muscidae: Dipptera) - Rizwanul Haq; M.farhan Ullah Khan; Ehtesham ul Haq (Journal of Basic & Applied Sciences, 2012)
Lead is significant environmental pollutant which contaminates food, soil, water, and air. Insects too are influenced easily by such pollutants, therefore present study have been designed to study the influence of lead (as lead acetate) on external morphology of Musca domestica. The different concentrations of lead acetate, i.e., 0.25 mg., 0.5 mg, and 01 mg per ml in diet of Musca domestica, were added ad effects were observed after 48 hours. Results revealed that in addition to abnormalities and malformation the larvae, morphological changes in adults were observed such as elongated and de-shaped wings and elongated and folded legs. Some other structural abnormalities of larvae and pupal shape were also observed (tell briefly what were those changes. Thus the Diptera flies present a useful model for the rapid screening of the environmental hazards due to lead contamination, which exerts a definite physiological and morphological effect on these flies.